Anticancer Potential of Ferns from Uttarakhand Region - Gupta, Akhil; Sharma, Rakesh; Kumar, Neeraj; Bansal, Mayank; Dudhe, Rupesh; Gupta, Shiv Kumar (Journal of Biomedical and Pharmaceutical Research, 2023)
The current study deals with the anticancer potential of ferns in Uttarakhand region. The ferns are widely used by the local people of the Uttarakhand Himalaya. The present study documents anticancer and antioxidant activity of some fern plants, which are prevalent in study area along with botanical name, family, chemical constituents and their activity for medicinal use. Among all the pteridophytes examined taxa from the Pteridaceae, Polypodiaceae, and Adiantaceae exhibited significant medicinal activity. Based on our review, many pteridophytes have properties that could be used in alternative medicine for treatment of cancer. Keywords: Anti-cancer, Anti-oxidants, Ferns, Uttarakhand.